The DianaWeb cohort during the first COVID-19 lockdown: changes in eating behaviour in women with breast cancer - Acito, Mattia; Natalucci, Valentina; Rondini, Tommaso; Gargano, Giuliana; Emili, Rita; Moretti, Massimo; Barbieri, Elena; Villarini, Anna; Villarini, Milena (Acta Biomedica Atenei Parmensis, 2023)
Background and Aim of the Work: Home confinement during the first wave of COVID-19 subverted people’s routines and generated a lot of stress among individuals. In addition to the ‘pure’ mental health consequences—a major public health concern, itself—this stressful situation led to a risk of worsening eating behaviours. The aim of this study was to investigate the potential deterioration of dietary habits in a cohort of women with breast cancer (BC). Methods: We used data from 781 women with BC enrolled in the DianaWeb project. We used validated questionnaires to collect data concerning socio-demographic/anthropometric parameters, quality of life (QoL), lifestyle and the change in dietary habits before and during the lockdown period (December 2019 and June 2020). Results: Data showed that psychiatric treatment, QoL and health perception significantly affected the food choices of the cohort (p = 0.048, p=0.002, and p=0.001, respectively), decisively contributing to a worsening in their eating behaviour. Moreover, sedentary behaviour during the lockdown also influenced food choice (p = 0.010): individuals who increased their sedentary behaviour were more likely to decrease their intake of recommended foods (p = 0.033). Conclusions: In summary, emotional state and mood—here investigated as QoL and health perception—definitely affected dietary habits in women with BC in the first COVID-19 lockdown. Given the centrality of correct eating behaviour in BC management, psychological aspects should not be contemplated merely as confined mental health matters but should be definitely taken into consideration also as factors that seriously affect an individual’s healthy lifestyle.